2023
DOI: 10.1186/s12885-023-11013-y
|View full text |Cite
|
Sign up to set email alerts
|

Photon and Proton irradiation in Patient-derived, Three-Dimensional Soft Tissue Sarcoma Models

Abstract: Background Despite their heterogeneity, the current standard preoperative radiotherapy regimen for localized high-grade soft tissue sarcoma (STS) follows a one fits all approach for all STS subtypes. Sarcoma patient-derived three-dimensional cell culture models represent an innovative tool to overcome challenges in clinical research enabling reproducible subtype-specific research on STS. In this pilot study, we present our methodology and preliminary results using STS patient-derived 3D cell cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In most studies, organoids are prepared from surgery specimens in order to have sufficient material, and drug screening is performed a few days before starting patient treatment. Several reports have established correlations between responses in PDOs and responses in patients, including disease trajectory, and have helped to characterise the landscape of drug resistance [100][101][102][103]. A larger collection of tissues (194 specimens from 126 sarcoma patients, spanning 24 distinct subtypes including metastases) was recently evaluated to establish whether they could be used to predict treatment sensitivity.…”
Section: Organoid Assays To Test Targeted Drugs and Chemotherapy In P...mentioning
confidence: 99%
“…In most studies, organoids are prepared from surgery specimens in order to have sufficient material, and drug screening is performed a few days before starting patient treatment. Several reports have established correlations between responses in PDOs and responses in patients, including disease trajectory, and have helped to characterise the landscape of drug resistance [100][101][102][103]. A larger collection of tissues (194 specimens from 126 sarcoma patients, spanning 24 distinct subtypes including metastases) was recently evaluated to establish whether they could be used to predict treatment sensitivity.…”
Section: Organoid Assays To Test Targeted Drugs and Chemotherapy In P...mentioning
confidence: 99%
“…They assessed a decrease in tumor cell viability at different time points (four and eight days after treatment) using increasing doses of photon and proton radiation. PD3D therefore could be a valuable tool to facilitate translational studies toward individualized subtype-specific radiotherapy in STS patients [55].…”
Section: Established Cancer-derived Cell Linesmentioning
confidence: 99%
“… 2 5 Although the physical properties of the proton beam appear more attractive, recent in vitro and clinical head-to-head studies showed no difference in tumor control when protons or photons were applied. 6 , 7 In stereotactic radiotherapy (SRT), the radiation is delivered either as a single dose SRT (sdSRT) at high dose (e.g. 25 Gray [Gy]) 8 or as fractionated SRT (fSRT), consisting of several lower dose fractions (e.g.…”
mentioning
confidence: 99%